On the gut content, community structure and potential using of butterfly fishes (Chaetodontidae) as bioindicators for coral reefs status - Quan, Nguyen Van (Academia Journal of Biology, 2012)
Based on analysis of the gut content for 9 common Chaetodontids and results of study on the community structure of the butterfly fishes (Chaetdontidae) have been carried out at Nha Trang bay Marine Protected Area in 2004-2005. It pointed out the potential using of several Chaetodontids as the obligate coral feeders, contributed as the bioindicators for coral reefs status. Though, there were no correlations found between the live coral cover with the species richness but a strong linkage has been discovered between abundance variation and coral live cover at most of the transect sites (p < 0.05). Two coralivorous species Chaetodon trifasciatus and Chaetodon trifascialis (R2 = 0.6 vµ 0.67) were presented as the bioindicator species that may be used for monitoring purpose of the coral reefs by the impacts of natural and human induced. However, an integrated research program should be implemented at the broader scales (variation of reef types, diversity of geographic location) for gathering a checklist of potential Chaetodontid species. They may be the feasible keystone species for the multiple purposes such as monitoring of coral reefs and assessment of the management effectiveness after establishment of the marine protected area. Thus, it contributes science sounds for management of coral reef ecosystem in Vietnam.